Effectiveness of Safety Vests in Pediatric Horseback Riding - Hessler, C.; Eckert, V.; Vettorazzi, E.; Meenen, N.; Jürgens, C.; Schult, M.; Flamme, C.; Herberhold, H.-J.; Madert, J.; Ekkernkamp, A.; Lockemann, U.; Püschel, K.; Pohlenz, P. (Klinische Pädiatrie, 2012)
Despite the benefit of safety vests to the reduction of torso injuries in children and adolescents is unclear, its’ use is recommended. The aim of the present study is to determine the effectiveness of safety vests actually used in pediatric equestrian activities.In this case-control-study, we analyzed the accidents of 92 riders aged 18 or younger who fell off a horse onto his/her torso during a period of 18 months. Data were gathered from the clinical records. Additionally, a questionnaire was administered on the day of trauma by the patients and/or their parents.The cases comprised 31 patients who sustained torso injuries. The controls were 61 riders with injuries of other body parts than to the torso. Safety vest use was not associated with a lower risk of torso injuries (OR=1.18, 95% CI (0.50, 2.81), p=0.707). Post hoc power analysis revealed that within such a setting an odds ratio of 0.266 could be found with a power of 80%.This study is not able to show an association between wearing a torso protector and protection from torso injuries, probably due to confounding. We did not detect a high effect of safety vest usage in our study population. Whether the development of a new generation of safety vests might be more effective remains unclear. An effective vest should be adapted to the requirements of children and adolescents and should protect the thorax and abdomen, but also the cervical and the lumbar spine.
Keywords: children; adolescent; horseback riding; torso injuries; safety vests